Euthanasia From the Perspective of Criminal Law and Human Rights - Arthawidjaja, I Gusti Lanang; Muhibbin, Moh.; Parmono, Budi (Jurnal Locus Penelitian dan Pengabdian, 2025)
With the development of technology and science in the medical field, death does not always occur suddenly; instead, it can occur according to plan. Such an act, defined as the killing of a person at a predetermined time and place, is called euthanasia. This practice remains controversial and has not been adequately resolved by various parties. This study aims to analyze euthanasia from the perspective of human rights and criminal law applicable in Indonesia. The research method employed is a normative theoretical approach, encompassing primary, secondary, and tertiary legal materials. The findings of this study indicate that euthanasia, as regulated in Indonesian society, disregards an individual's right to life and is, therefore, not permitted. Although euthanasia is not explicitly recognized in Indonesian law, several provisions could potentially criminalize it, such as Articles 344 and 345 of the old Criminal Code or Kitab Undang-Undang Hukum Pidana (KUHP) and Articles 461 and 462 of the new KUHP. The process of legislation and legal reform, particularly concerning euthanasia, must continue to be guided by Pancasila and the 1945 Constitution of the Republic of Indonesia, while also considering the religious and cultural norms prevailing in Indonesian society.